Exploring Probability of Detection (POD) analysis in nondestructive testing: a comprehensive review and potential applications in phased array ultrasonic corrosion mapping - Jan, Lean Tai; Hameed Sultan, Mohamed Thariq; Shahar, Farah Syazwani; Yidris, Noorfaizal; Basri, Adi Azriff; Md Shah, Ain Umaira (UPM Press, 2024)
In nondestructive testing (NDT), ensuring defect detection, measurement accuracy, and reliability guarantees various components’ structural integrity and safety. The Probability of Detection (POD) concept has emerged as a fundamental measure of the effectiveness of an inspection technique in identifying defects. Since NDT plays a crucial role in aerospace, manufacturing, and infrastructure industries, enhancing POD has become critical. POD refers to the likelihood that a flaw or defect of a certain size will be detected using the NDT technique. The “â versus a” and the “hit/miss” methods are particularly notable among the commonly employed POD estimation methods. The POD curve is determined based on crack size measurements in the “â versus a” approach, typically used in ultrasonic testing. On the other hand, the “hit/miss” method establishes the POD curve by analysing binary outcomes, where a “hit” signifies successful detection and a “miss” denotes detection failure. This review focuses on POD in the context of NDT, specifically in phased array ultrasonic corrosion mapping (PAUCM), to uncover current uncertainty parameters and explore an innovative avenue for enhancing POD assessment by incorporating the material surface temperature as an additional parameter.